Near infra-red labelling and tracking of corneal endothelial cells in-vivo - Bhogal, Maninder (2023)
Following corneal transplantation, there is an initial, rapid decline in corneal endothelial cells (CECs) following surgery. Direct imaging of post-transplantation endothelial cells is only possible weeks after surgery and with a limited field of view. We have developed a labelling approach using 1,1'-dioctadecyl-3,3,3',3'-tetramethylindotricarbocyanine iodide (DIR) dye solution, that enables tracking of labelled CECs in vivo for at least 1 month. Initial in vitro optimization, with assessments of dye concentration on fluorescence, cellular toxicity and cell migration, performed in propagated primary CECs. Subsequently, in vivo evaluation of cellular labelling was assessed within a rabbit wound healing model. Finally, real-time visualization of human cadaver donor tissue incubated in DIR transplanted into rabbits was achieved using a clinical confocal microscope. Results revealed detectable fluorescence increased with concentration to a plateau of 100 µg/ml, with no toxicity of CECs at any concentration evaluated. DIR-labelled CECs were detectable in vivo up to 1 month, and transplanted labelled donor graft could be visualized and were trackable in vivo. Acute endothelial rejection in 1 rabbit was evidenced by detectable DIR positive cells within the anterior chamber. DIR imaging allowed for detailed imaging of the transplanted human corneal endothelium, and enabled non-invasive observation of the corneal endothelial morphology following transplantation.